Pigtail Catheter In The Management Of Liver Abscess (Journal of Surgical Sciences, 2014)
Background: Liver abscess is a common condition in the rural population of our country due to overcrowding and poor hygiene. Though conservative treatment plays a major role, refractory patients can be successfully treated with minimally invasive approach.Objectives: To evaluate the prospect of sono-guided percutaneous catheter drainage for liver abscess patients not responding to conservative treatment.Methods: It is a prospective study carried out at Dhaka Medical College and Hospital during the period January 2005 to June 2006 among patients with liver abscess that were admitted in different surgery and medicine units. A total of 35 patients concluded the sample. Evaluation of the patients was based on history, physical examination and relevant investigations. Sono-guided percutaneous catheter was introduced and patients were followed up for two weeks.Results: In our study 35 patients underwent pigtail catheter drainage that were refractory to conservative treatment or needle aspiration. During the time of the procedure, 22 patients were having high fever; rest 13 patients were in an afebrile state. Many of the patients had history of weight loss, anorexia, nausea, vomiting and upper abdominal pain. Following insertion of catheter patients who were pyrexic, fever subsided in two to three days and never back during the postoperative period and follow up. Antimicrobials were changed according to the report of the culture and sensitivity of the aspirate that was done routinely. Out of the rest 13 patients, who were in an afebrile state and their abscess cavity did not reduce in size despite drug treatment and needle aspiration, improved significantly following catheterization. Follow up Ultrasonography showed reduction of the size of the abscess cavity with no or little collection, the abscess was in the resolving state and the patient began to feel better.Conclusions: With a very low morbidity and zero mortality rate, minimum treatment costs and early return to regular life style proved this minimally invasive procedure to be a rational treatment option for liver abscess (>5 cm).Journal of Surgical Sciences (2014) Vol. 18 (1) : 3-8